MENGUAK KESENJANGAN ANTARA PASAR MODERN DAN PASAR TRADISIONAL - Khusnul Khotimah; Dadang Hartanto; Nuruh Alipah (Kompetensi (Competence : Journal of Management Studies), 2018)
ABSTRACTThis study is entitled "Perception of the Community Against Modern Markets" This study presents two formulations of the problem, namely whether the influence of modern markets on the social life of the community and how the public perception of the modern market in Kamal, Bangkalan Regency. Based on the formulation of the problem, this study has a purpose to see people's perception of the existence of a modern market in Kamal, Bangkalan Regency. To find out the influence of the modern market on people's social life in Kamal, Bangkalan Regency. To know the development of capitalism in Indonesia by connecting capitalism and the development of modern markets. This type of research is qualitative descriptive, using several informants to conduct interviews and observations. The source of the data used is the primary source, namely information that comes from direct observation to the research location by means of observation and interviews. While secondary sources are data obtained from documentation or library studies to complete primary data. Data collection is carried out through field research through observation, interviews, and documentation.